Implementing a no-fault scheme for motor vehicle accidents in Malaysia: issues and challenges - Nicholson, Charles; Amin, Naemah (AENSI Publications, 2014)
Experiences with the operation of the traditional tort law as a personal injury compensation mechanism have convinced many jurisdictions of its incapability to function as a fair, just and effective regime in addressing many of the concerns and plight of injured victims of motor vehicle accidents. In Malaysia, calls for reform of the civil justice system made in good faith from concerned individuals and consumer rights groups have existed since the early 1980s and they insisted for the replacement of present system with an appropriate statutory no-fault compensatory model. Under the new scheme benefits to the injured would be provided automatically regardless of who was responsible for the accident thus avoiding the need for costly and potentially stressful and lengthy litigation to obtain compensation. Social justice and community care for the beneficiaries of the scheme are the essence of modern no-fault systems which have taken precedence over conventional notions of individual responsibility and morality that underpin the present fault-based structures. Nonetheless the question arises whether the workability of the scheme in other jurisdictions would produce a similar impact in the Malaysian context. There are obviously a number of practical considerations that need to be taken into account before implementing an alternative compensation scheme. This article aims to examine some of the principal issues and challenges that are likely to be faced with the implementation of a no-fault compensatory model for injured road users. It also attempts to address several concerns and doubts as to the viability of implementing such a scheme in Malaysia.